Cases on technology innovation : entrepreneurial successes and pitfalls - Becker, S. Ann.; Niebuhr, Robert E. (Hershey, PA : Business Science Reference, 2010)
'This book presents cases on theory, research, and practice in the areas of technology transfer, innovation, and commercialization, offering illustrations and examples of entrepreneurial successes and pitfalls in university, industry, government, and international settings'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Technology transfer -- Case studies; Technological innovations -- Case studies; Research, Industrial -- Case studies; Entrepreneurship -- Case studies